Individuelle Förderung von Schülerinnen und Schülern mit Legasthenie im Fremdsprachenunterricht - Rybarczyk, Renata (Glottodidactica, 2015)
Dyslexic students have significant problems with learning a foreign language. Foreign language (FL) learning is built upon the native language (L1). The skills such as phonological/ orthographic, syntactic and semantic competences in the native language form the foundation for foreign language learning (and FL aptitude). The strength of the native language codes considerably determines the extent to which a learner can become proficient in a foreign language. Weak L1 skills inhibit FL proficiency development. That is why it is essential to provide dyslexic students with special support in foreign language classes.